Switching the surface homochiral assembly by surface host–guest chemistry. Issue 80 (27th September 2017) - Li, Shu-Ying; Chen, Ting; Yue, Jie-Yu; Wang, Dong; Wan, Li-Jun
Abstract : Surface chirality could be switched by host–guest chemistry. Abstract : We combine chiral amplification and host–guest chemistry to demonstrate an approach to achieve a switchable chiral assembly. After the addition of the guest coronene, homochiral honeycomb patterns transform into host–guest sunflower structures, in which supramolecular chirality is modulated dramatically.